2018
DOI: 10.1051/matecconf/201815005065
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s Behaviour with Coronary heart desease Viewed from Socio-Cultural aspect of Aceh Society in Zainoel Abidin Hospital

Abstract: Coronary heart disease (CHD) is a chronic inability of heart to draw an adequate blood on myocardium due to specific problem in coronary artery. When the artery that supplies myocardium is interrupted, thus the heart is unable pumping the blood effectively to fill up an adequate blood perfusion to vital organs and other peripheral tissues. If the perfusion is impaired in time of oxygenation, the patient will threatened by a sudden death. This is a quantitative, analytical and observational research with a desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
0
6
0
4
Order By: Relevance
“…The discrepancy could be due to other variables, such as poverty, the fact that the participants in Mousaeipour et al’s [ 82 ] study were women and legislation governing the trade and use of drugs. Self-medication practices can develop in different countries with varying patterns, given that most human behaviors are influenced by ideas, ideologies and conventions depending on the cultural and social environment of the area [ 83 ]. Therefore, to draw meaningful conclusions, it is important to conduct such studies among various demographics.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy could be due to other variables, such as poverty, the fact that the participants in Mousaeipour et al’s [ 82 ] study were women and legislation governing the trade and use of drugs. Self-medication practices can develop in different countries with varying patterns, given that most human behaviors are influenced by ideas, ideologies and conventions depending on the cultural and social environment of the area [ 83 ]. Therefore, to draw meaningful conclusions, it is important to conduct such studies among various demographics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, improving health literacy is part of the Healthy People 2020 program (43). Furthermore, in the strategic document of the health system policies of the Islamic Republic of Iran, the promotion of health information, accountability, structured ability, and participation of the individual, family and society in provision, preservation, and promotion of health are of the priorities of the health system, using the capacity of cultural, educational, and media entities, and organizations under the supervision of the Ministry of Health, Treatment, and Medical Education (29). Generally, the results of this study showed significant differences in both the health literacy level and self-medication behaviors and the relationship between these two components with the results of similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be said that they play a very significant role in family health care. Considering that most human behaviors are influenced by beliefs, creed, and customs based on the cultural and social context of societies (29), self-medication behaviors can also appear in different societies with different patterns. The researchers in the present study did not find a similar study in Iran investigating the relationship between health literacy and the occurrence of self-medication behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…This research uses a type of quantitative research that uses a pre-test and post-test one group design (Notoatmodjo et al, 2018), with a Quasi-Experimental design without a control group that compares the evaluation results before and after treatment of respondents. The research population was all 32 mothers who had LBW babies who were treated at the Pratama Bunda Patimah Clinic.…”
Section: Methodsmentioning
confidence: 99%